The Role of Principal Leadership in Enhancing Educational Empowerment in Junior High Schools - Pri An Nissa Firdaus; Chusniatun (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2026)
Education plays a strategic role in determining the quality of human resources and national competitiveness. Educational quality is inseparable from the role of principal leadership as the main driver in school management and empowerment. Schools function not only as places for academic learning, but also as institutions for character formation and student independence. SMP Muhammadiyah 7 Colomadu Excellence Program once experienced a decline in quality marked by decreasing student enrollment, limited facilities and infrastructure, weak governance, and low public trust. This study aims to describe the role of principal leadership in enhancing educational empowerment, and to identify supporting and inhibiting factors in the process. This study uses a qualitative approach with field research methodology. Data were collected through observation, interviews, and documentation. The results show that principal leadership plays an important role in driving change through strategic decision-making, school management restructuring, strengthening organizational culture, and implementing innovative programs relevant to school and community needs. Supporting factors include visionary leadership, shared vision among stakeholders, external environmental support, and increased teacher professionalism. Inhibiting factors include limitations in human resources, facilities and infrastructure, administration, as well as communication and supervision constraints. Adaptive leadership is key to realizing sustainable educational empowerment.